Spatial allocation and sustainable development: a study of production-living-ecological spaces in the Yangtze River Delta - Li, Shangbo; Chen, Yong; Huang, Qinshi (Frontiers in Environmental Science, 2025)
The overlap and irrational distribution of Production-Living-Ecological Spaces (PLES) has disrupted traditional urban-rural development patterns and impeded regional integration. This study, focusing on the Yangtze River Delta region, introduces a PLES framework and constructs a classification system based on multitemporal land use data. The CA-Markov model was employed to simulate land use changes for the years 2030 and 2040. By quantifying and analyzing the number, distribution, and transitions of PLES categories, the study identifies spatial and temporal patterns and evaluates the coupling coordination of the various PLES components. The key findings are as follows: (1) The proportion of Production-Living Space (PLS) increased from 9% in 2000 to 14% in 2020, with projections indicating further growth to 15% by both 2030 and 2040, while Ecological Space (ES) remained relatively stable; (2) The coupling coordination between the stages of PLES evolved from mild disharmony to weak coordination, reflecting a shift from localized improvements to broader, more integrated spatial development; (3) The spatial distribution of PLES coupling exhibited significant heterogeneity, characterized by higher values in the eastern region, lower values in the western region, and a pattern of concentration in the north and dispersion southward. These findings contribute to a deeper understanding of the spatial dynamics of PLES and provide strategic recommendations for optimizing the spatial layout of the Yangtze River Delta urban agglomeration, thereby promoting sustainable urban development.